RESPONS PADI GOGO (Oryza sativa L.) TERHADAP PEMBERIAN KOMPOS TANDAN KOSONG KELAPA SAWIT (TKKS) DAN PUPUK FOSFOR PADA TANAH ULTISOL - Zalukhu, Juniaro; Murniati, Murniati; Idwar, Idwar (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
Upland rice is a rice producing food crop that needs to be increased by utilizing Ultisol soil. This soil has low organic matter and P is fixed by Al, so it is necessary to provide TKKS compost and phosphor fertilizer. This study aims to determine the combination of TKKS compost with phosphor fertilizer and each of the main factors that can support the growth and yield of upland rice. This research was conducted at the University of Riau Faculty of Agriculture Experimental Garden, starting from February 2018 to June 2018. This research was conducted using factorial randomized complete design. The first factor was TKKS compost (0, 5, 10, and 15) ton.ha-1, the second factor was phosphorus fertilizer (36.8, 46.0, 55.6, and 64.4) kg P2O5.ha-1. Observation parameters: plant height, number of productive tillers, harvest age, panicle length, number of grains per panicle, percentage of rice grain, weight of empty grain and weight of milled dry grain and weight of 1000 grains of grain. The data obtained were statistically analyzed by variance analysis and further duncan’s multiple range tests (DMRT) at the level of 5%. TKKS compost 15 tons.ha-1 gaves better results for all parameters except the percentage of rice grain and weighs 1000 grains. Phosphor fertilizer 64.4 kg P2O2.ha-1 gave better results for parameters of plant height, panicle length, number of seed grains, and weight of milled dry grain per clump. Combination TKKS compost 15 tons.ha-1 with phosphorus fertilizer 64.4 kg P2O2.ha-1 and 10 tons.ha-1 with 46.0 kg. P2O2.ha-1 provides better results compared to other treatments for all parameters except the percentage of rice grain and weight of 1000 grains. Keywords: TKKS Compost, Phosphorus Fertilizer, Upland Rice and Ultisol